Wheat flour fortification and human health - Pachón, Helena (Burleigh Dodds Series in Agricultural Science, 2021)
Using varied study designs (none of which can confirm causality), investigators assessed the health impact of wheat flour fortification after it was implemented at large scale in countries. Folic acid was the most studied nutrient and the most studied outcomes were neural tube defects, cancer, folate status, folate deficiency, anemia, iron deficiency, iron status, hemoglobin and iron-deficiency anemia (IDA). For all of these outcomes except IDA, the majority of studies showed improvements after fortification. For some of the outcomes (cancer, anemia, hemoglobin, folate deficiency), there were studies that indicated health outcomes worsened after fortification. The discrepant results for cancer may be due to years since fortification initiated and sample size differences. The preponderance of the evidence suggests that wheat flour fortification improves many health outcomes. Because fortification may also be associated with negative health outcomes such as cancer, health monitoring should continue to assess these outcomes in countries with fortification.